Escape or encouragement? The role of media entertainment during the COVID-19 pandemic in China - Deya Xu; Ge Zhu; Fang Wu; Zhiwei Xu (Humanities & Social Sciences Communications)
Abstract During the COVID-19 pandemic, Chinese people could use media entertainment to relieve the stress associated with the situation. This study examines whether media entertainment helped Chinese people escape from the flood of pandemic-related information or encouraged them to take preventive measures and protect themselves during the COVID-19 pandemic. Based on the social amplification of risk framework, this study investigates the role of media entertainment in public communication during the COVID-19 pandemic. With the assistance of a Chinese online survey platform, 833 respondents were recruited. The findings reveal that social interaction, recognition needs, and entertaining gratification were positively related to entertainment use, indicating that Chinese people actively sought enjoyment and met their social needs through entertainment media content during the quarantine but did not use such media to avoid unpleasant information concerning the pandemic. Media entertainment use had direct effects in terms of increasing the likelihood of Chinese people engaging in preventive behaviors, but its indirect effects through emotions were limited.